2022
DOI: 10.1038/s41467-022-34689-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis identifies osteosarcoma subtypes with distinct prognosis indicating stratified treatment

Abstract: Osteosarcoma (OS) is a primary malignant bone tumor that most commonly affects children, adolescents, and young adults. Here, we comprehensively analyze genomic, epigenomic and transcriptomic data from 121 OS patients. Somatic mutations are diverse within the cohort, and only TP53 is significantly mutated. Through unsupervised integrative clustering of the multi-omics data, we classify OS into four subtypes with distinct molecular features and clinical prognosis: (1) Immune activated (S-IA), (2) Immune suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 98 publications
5
30
0
Order By: Relevance
“…Moreover, our study validate that the BM-MSCs with co-deletion of WWOX and p53 are tumorigenic compared to p53 deletion alone although with a later latency as compared with BM-MSCs harboring p53 and Rb co-deletion 34 . Furthermore, our DKO yBM model exhibited early molecular pathway enrichment, which is consistent with a recent multi-omics analysis performed on human OS clinical samples 35 . Interestingly, Myc amplification and overexpression of Myc targets were detected and correlated with a worse prognosis, indicating the crucial role of Myc in osteosarcomagenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, our study validate that the BM-MSCs with co-deletion of WWOX and p53 are tumorigenic compared to p53 deletion alone although with a later latency as compared with BM-MSCs harboring p53 and Rb co-deletion 34 . Furthermore, our DKO yBM model exhibited early molecular pathway enrichment, which is consistent with a recent multi-omics analysis performed on human OS clinical samples 35 . Interestingly, Myc amplification and overexpression of Myc targets were detected and correlated with a worse prognosis, indicating the crucial role of Myc in osteosarcomagenesis.…”
Section: Discussionsupporting
confidence: 89%
“…We used different methods to identify the heterogeneity of OS, but partially with similar molecular features and clinical prognosis, such as Immune activated (S-IA) and our immunogenic subtype both have immunological traits and better clinical prognosis. Their Immune suppressed (S-IS) subtype has activated adipogenesis and fatty acid metabolism-related pathways and encodes the fatty acid scavenger receptor CD36 which is in line with our adipocyte-like subtype [64]. We explored the heterogeneity and the underlying mechanism of OS that could help to provide better, customized therapy.…”
Section: Discussionmentioning
confidence: 90%
“…Future research will seek to identify and validate novel functional neoantigens that may aid in the killing of OS tumor cells in vivo , as we demonstrated that vitamin D 3 disproportionately induced the upregulation of NMD-target genes in OS cells. In addition, it appears that calcipotriol may function similarly to 1,25(OH) 2 D, with enhanced effects on cell migration and gene expression across multiple pathways, such as EMT and NMD, within subtypes of OS cells 113 .…”
Section: Discussionmentioning
confidence: 99%